Is cork oak (Quercus suber L.) woodland loss driven by eucalyptus plantation? A case-study in southwestern Portugal - Costa, a; Madeira, M.; Santos Lima, J.; Costa A, Madeira M.; J, Santos Lima (iForest - Biogeosciences and Forestry, 2014)
Mediterranean landscapes with open cork oak (Quercus suber L.) woodlands have recently experienced drastic changes in southwestern Portugal. Changes in agricultural activities, the traditional driver of the economy in this region, led to new land uses such as long-term set aside (shrublands) and eucalyptus plantations. A study was conducted on the oak woodland landscape dynamics over a 50-year period (from 1958 to 2007) in order to assess the effect of different biophysical conditions on landscape spatial changes, and to identify the resilience of lanscape composition to different disturbances (e.g., socio-economic changes and wildfires). Land use changes over two consecutive periods (1958-1995 and 1995-2007) were inferred by spatial analysis of land cover data (aerial photographs) and related to landscape physical attributes (slope and soil type). A transition matrix of four vegetation land-cover classes was obtained, allowing the assessment of the landscape composition changes bewteen the two above periods. Results showed that lansdcape in 1958 was largely occupied by open farmland, with large patches of open oak woodlands on steep slopes surrounding watercourses. Open farmland and shrubland drastically declined from 1958 to 1995, while eucalyptus plantation exhibited a dramatic expansion. Although large areas of cork oak forest turned into eucalyptus plantation, the net loss of oak forest was low and counterbalanced by its increment on former open farmland. The occurrence of a wildfire in 2003 promoted a dramatic decrease in cork oak woodlands, which mostly turned into shrubland. However, shrubland may be considered “safe sites” for ecological succession, ensuring natural cork oak regeneration and the colonization of neighboring areas.
Keywords: agroforestry systems; Eucalyptus Plantations; evergreen oak woodlands; Land Cover; Mediterranean Climate Region; Quercus suber L.

An approach to cork oak forest management planning: a case study in southwestern Portugal - Costa, a; Oliveira, A C; Vidas, F; Borges, J G (European Journal of Forest Research, 2009)
This paper presents results of research aiming at the development of tools that may enhance cork oak (Quercus suber L.) forest management planning. Speciﬁ- cally, it proposes an hierarchical approach that encompasses the spatial classiﬁcation of a cork oak forest and the temporal scheduling of cork harvests. The use of both geographical information systems and operations research techniques is addressed. Emphasis is on the achievement of cork even ﬂow objectives. Results from an application to a case study in the Charneca Plioce´nica of Ribatejo in southern Portugal encompassing a cork oak forest extending over 4.8 thousand ha are discussed. They suggest that the proposed approach is capable of effective spatial classiﬁcation of cork oak management units. They further suggest that it may be used to select optimal cork even ﬂow scheduling strategies. Results also show that the proposed approach may lead to a substantial increase in net present value when compared to traditional approaches to cork oak forest management planning.
Keywords: cork harvesting; Cork oak forest management; Harvest scheduling; Linear programming; Quercus suber L.

An approach to cork oak forest management planning: a case study in southwestern Portugal - Costa, a; Oliveira, A C; Vidas, F; Borges, J G (European Journal of Forest Research, 2009)
This paper presents results of research aiming at the development of tools that may enhance cork oak (Quercus suber L.) forest management planning. Speciﬁ- cally, it proposes an hierarchical approach that encompasses the spatial classiﬁcation of a cork oak forest and the temporal scheduling of cork harvests. The use of both geographical information systems and operations research techniques is addressed. Emphasis is on the achievement of cork even ﬂow objectives. Results from an application to a case study in the Charneca Plioce´nica of Ribatejo in southern Portugal encompassing a cork oak forest extending over 4.8 thousand ha are discussed. They suggest that the proposed approach is capable of effective spatial classiﬁcation of cork oak management units. They further suggest that it may be used to select optimal cork even ﬂow scheduling strategies. Results also show that the proposed approach may lead to a substantial increase in net present value when compared to traditional approaches to cork oak forest management planning.
Keywords: cork harvesting; Cork oak forest management; Harvest scheduling; Linear programming; Quercus suber L.

Quality characterization of wine cork stoppers using computer vision - Costa, a; Pereira, H (JOURNAL INTERNATIONAL DES SCIENCES DE LA VIGNE ET DU VIN, 2005)
Image analysis techniques were applied on the surface of wine cork stoppers (tops and lateral cylindrical surface) of seven commercial quality classes to characterize their porosity. An increasing trend from the best to the worst quality classes was found for features related to area of pores (i.e. maximum length and width or pore maximum area) and concentration variables (i.e. porosity coefficient or number of pores per 100 cm(2)). Shape variables were rather constant and mean values showed no differences between quality classes. Variation of the pores characteristics within each quality class was large especially in the mid-quality range. Therefore there were no statistically significant differences to allow the isolation of the all quality classes and overlapping was particularly important in the medium-quality classes. The reduction of grading into only three quality classes allowed to isolate statistically different subsets based on porosity coefficient and number of pores per 100 cm(2). These variables can be selected for further development into quality grades specification of wine cork stoppers.
Keywords: computer imaging; quality classes; wine cork stoppers

The effect of cork-stripping damage on diameter growth of Quercus suber L. - Costa, a; Pereira, H; Oliveira, A (Forestry, 2004)
The Mediterranean cork oak (Quercus suber L.) agro-forestry system is oriented towards cork production, with cork being extracted from tree stem and branches as planks by cutting with an axe and stripping off. The effect of damage to the tree during cork stripping was studied in cork oaks, weakened by wounding, by following the diameter growth and its seasonality during a 9-year production cycle, and comparing them with healthy cork oaks. Tree wounding decreased diameter growth during the following cycle, e.g. 8.5 mm a−1 and 9.8 mm a−1 for weakened and healthy trees, respectively, mostly in the 2 years immediately following the cork stripping. The beginning of annual growth in spring and the occurrence of the highest increments in June–August were delayed by about 1 month in the weakened trees. The cork produced by weakened trees was reduced by 13 per cent in thickness, with average cork ring widths of 3.3 mm a−1 vs. 3.8 mm a−1 for healthy trees.
10.1093/forestry/77.1.1
Keywords: Cork Production; stripping; wound responses (PG)

The effect of cork-stripping damage on diameter growth of Quercus suber L. - Costa, a; Pereira, H; Oliveira, A (Forestry, 2004)
The Mediterranean cork oak (Quercus suber L.) agro-forestry system is oriented towards cork production, with cork being extracted from tree stem and branches as planks by cutting with an axe and stripping off. The effect of damage to the tree during cork stripping was studied in cork oaks, weakened by wounding, by following the diameter growth and its seasonality during a 9-year production cycle, and comparing them with healthy cork oaks. Tree wounding decreased diameter growth during the following cycle, e.g. 8.5 mm a−1 and 9.8 mm a−1 for weakened and healthy trees, respectively, mostly in the 2 years immediately following the cork stripping. The beginning of annual growth in spring and the occurrence of the highest increments in June–August were delayed by about 1 month in the weakened trees. The cork produced by weakened trees was reduced by 13 per cent in thickness, with average cork ring widths of 3.3 mm a−1 vs. 3.8 mm a−1 for healthy trees.
10.1093/forestry/77.1.1
Keywords: Cork Production; stripping; wound responses (PG)

Variation in cork production of the cork oak between two consecutive cork harvests - Costa, a; Oliveira, A C (Forestry, 2001)
The variation in the cork produced by individual trees (Quercus suber L.) in three distinct locations, Mora, Alcácer do Sal and Benavente, is characterized by measurements made during two consecutive harvests of cork in the same trees. Particular emphasis is given to the variability in the weight of cork produced by individual trees and its mean caliper for the two strippings in each region. A good linear correlation between the tree circumference after the first stripping and the weight of the cork produced 9 years later as well as a poor linear correlation between the first variable and the caliper of the cork produced 9 years later is reported. A cork oak diameter curve is presented for each region, considering their two radial growths: the wood growth, which is cumulative, and the cork growth, which is the 9‐year growth.
10.1093/forestry/74.4.337
Keywords: Cork Production; Growth (PG); stripping; variability